Pendidikan Karakter Anak Dalam Pembelajaran Bahasa Indonesia (Children’s Character Education In Indonesia Language Learning) - Husna H; Siti Rukiyah; Missriani M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Character education is very important for the advancement of moral education in Indonesia. Character education is a form of human activity in which there is an action that educates and is intended for the next generation. By having a good character education, a person will have a strong moral foundation, good social skills, high motivation, and quality leadership abilities. This is what will help them to grow and develop into better individuals from all aspects. This study aims to determine the relationship between character education and Indonesian language learning and to determine the position and function of language in character education. This research was conducted using qualitative descriptive research method. The results of this study show that character education and Indonesian language learning have a very important relationship and have a relationship with each other. Then Indonesian has two very important positions, namely as the national language and the state language.